TRANSLATION OF INFINITIVE AND INFINITIVE STRUCTURES - Khudoyberganova Durdona ismail qizi (Лучшие интеллектуальные исследования, 2023)
Abstract: In this article infinitive and translation of infinitive structures are discussed. This features also belong to grammatical transformation. During the reading this article scientific facts and detailed examples are known. steps, topic, differences, aspects, translation, work, dictionary, analysis, comment, author, concept, change, method.